The Influence of Frirage Massage Training on Ankle Sprain Handling Skills - Nugroho, Singgih; Kuncoro, Bangkit; Suparmanto, Gatot; Afni, Annisa Cindy Nurul; Bambang Abdul Syukur (Viva Medika, 2023)
Exercise is an activity that provides physical and mental health benefits. Basketball is one of the most popular sports in society. In sports there is a risk of sprain ankle injuries. One of the efforts to improve individual skills in dealing with sprain ankle injuries is the masase frirage training program which is one of the techniques for handling sprain ankle injuries. The purpose of this study was to determine the effect of masase frirage training on handling skills of sprain ankle. This study used quantitative approach with a Quasi Experimental Design research method with pre and post tests without control. The sample size is 20 respondents by using total sampling technique. The research instrument used SOP masase frirage to assess the skills of the respondents. The results of data analysis obtained by using the Wilcoxon signed test that the significant value (p) is 0.000 which means that p <0.05. The conclusion of this study is that there is an effect of masase frirage training on handling skills of sprain ankle.